The Effects of Tropical Climate Stressor on Gamma Immunoglobulin Concentration of Serum and Colostrums of Dairy Cows of First and Second Parity - Westra, IGKP; Wahyudi, I (ANIMAL PRODUCTION, 2009)
The new born dairy calves serum containing extremely low antibodies (Ig) or nothing at all.Â  This means that their livability or mortality greatly depend on the antibody especially IgG of cowâs colostrums to sustain their passive immunity. An observation and analytical study was conducted to evaluate the effects of tropical climate stressor (TCS) on immunoglobulin gamma (IgG) concentration in three different climate locations in term of temperature (oC) and humidity (%). Those dairy farming locations were: (1) the cold or temperate climate in sub-districtÂ  Tutur, (2) the moderate climate in sub-districtÂ  Purwodadi and (3) the hot climate in sub-district Grati. Those three sub-districts are belong to District PasuruanâEast Java Province, Indonesia. For these purposes sample of 93 cows were determined using purposive sampling method and 29-33 blood samples (1.0 ml) of late pregnant cows (2â3 weeks pre partum) and colostrums samples (1,0 ml) from respective location were collected. Blood samples were measured for cortisol concentration (nmol/L) using radioimmunoassay (RIA) procedure and IgG serum and IgG kolostrum concentration (mg/ml)were measured using direct ELISA. The study was then set up to ensure factorial experimental design and conducted over summer season. SPSS for Window statistic program was applied to necessary statistical analysis. Results indicated: (1) Evidence of TCS significantly effected (P<0.05) the blood cortisol levels of the cows which was the lowest in the cold (22.28 mg/ml) and the highest in the moderate location (54.07 mg/ml),Â  (2) TCS was also affected IgG serum concentration (P<0.05) the lowest in moderate climate (4.76 mg/ml)Â  while between cold and hot climate was not different significantly, and (3) TCS did notÂ  decline concentration ofÂ  IgG colostrums (P>0.05) but a tendency that IgG colostrums concentration in hot climate was the lowest. The results suggest that low level of IgG in hot and moderate climates as being critical and efforts must find out to elevate IgG colostrums concentration to provide adequate passive immunity and at the same time preventing calves mortalities. (Animal Production 11(3): 143-148 (2009)Â Key Words: tropical climate stressor, cortisol, serum, colostrum, gamma immunoglobulin